The Latin American population in Spain and organ donation. Attitude toward deceased organ donation and organ donation rates. (21st January 2015) - Ríos, Antonio; López‐Navas, Ana I.; Navalón, Juan C.; Martínez‐Alarcón, Laura; Ayala‐García, Marco A.; Sebastián‐Ruiz, María J.; Moya‐Faz, Francisco; Garrido, Gregorio; Ramirez, Pablo; Parrilla, Pascual
Summary: The Latin American (LA) population has similarities with the Spanish population which makes its integration into Spanish society easier. Objective: to analyze the attitude toward organ donation among Latin American citizens residing in Spain, to determine the psychosocial variables which affect this attitude, and to examine the correlation between donation rates of LA citizens in Spain and in their countries of origin. A random sample of LA residents in Spain was taken and stratified according to the respondent's nationality ( n  = 1.314), in the year 2010. Attitude was assessed using a validated questionnaire (PCID‐DTO Dr Rios). The survey was self‐administered and completed anonymously. Statistical analysis: Student's t ‐test, the χ 2 test, and logistic regression analysis. There was a 94% completion rate ( n  = 1.237). Attitude toward donation was favorable in 60% of cases ( n  = 745), 12% ( n  = 145) were against, and 28% ( n  = 347) were undecided. The following variables were associated with attitude toward donation: sex ( P  = 0.038), level of formal education ( P  < 0.001), country of origin ( P  = 0.002), attitude toward the donation of a family member's organs ( P  < 0.001), having discussed donation with the family ( P  < 0.001), carrying out prosocial activities ( P  = 0.025), attitude toward cremation of the body ( P  < 0.001), attitude toward burial of the body ( P  < 0.001), attitude toward having an autopsy carried out ( P  < 0.001), previous experience of the organ donation and transplantation process ( P  < 0.001), fear of mutilation after donation ( P  < 0.001), knowledge that the Church has a positive attitude toward organ donation and transplantation ( P  < 0.001), knowledge of one's partner's attitude toward organ donation ( P  < 0.001), and a belief that one might need a transplant in the future ( P  < 0.001). The donation rates in this population group in Spain are higher than those recorded in their countries of origin (55.76 vs. <10 pmp; P  < 0.001). The attitude toward organ donation among LA citizens residing in Spain is slightly worse than that reported in the native Spanish population and is determined by many psychosocial factors. The donation rates of LA citizens in Spain are higher than those in their countries of origin.